ANALISA PERBANDINGAN METODE PEMBELAJARAN DENGAN HASIL CAPAIAN PEMBELAJARAN PRAKTIKUM ANATOMI DERMATOMUSKULOSKELETAL MAHASISWA FK UPN VETERAN JAKARTA - Diana Agustini; Yanti Harjono Hadiwiardjo; Ayodya Heristyorini (PROSIDING SERINA, 2021)
During the Covid-19 pandemic, first year medical students in class of 2020, who have experienced online distance learning since their senior year of high school, needed to adapt to learning basic medical science, including human anatomy. This study aims to compare academic results between medical students who did offline anatomy learning and those who did online by looking at their OSPE (Objective Structure Practical Examination) grades. Population for this study includes class of 2020 students at Faculty of Medicine, UPN Veteran Jakarta who learned DMS module online and class of 2018 students who learned offline. Sample size of this study is 300 students, selected through total sampling method. Results show that median grades were 80 for online anatomy learning and 60 for offline learning. Wilcoxon test showed P=0.0000 which means there is a significant difference between OSPE results from online and offline anatomy learning.